2005
DOI: 10.1590/s0004-282x2005000200010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental meningoencephalomyelitis by Encephalitozoon cuniculi in cyclophosphamide-immunosuppressed mice

Abstract: Encephalitozoonosis is an increasingly important opportunistic protozoan infection in immunocompromised individuals. This study aims to examine the development of an experimental Encephalitozoon cuniculi infection in the central nervous system of immunosuppressed mice. Adult Balb-C mice were inoculated intraperitoneally with E. cuniculi spores, treated with cyclophosphamide during the experimental period and killed from 15 to 75 days post-inoculation. Tissue samples were collected and processed for light and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…The action of betamethasone (1 mg/kg/day), which was administered before and after the inoculation of the T. canis eggs, was studied, and this drug had no immunosuppressor effect (Lescano et al 2004). The immunosuppressor effect of cyclophosphamide was observed in an infection by Encephalitozoon cuniculi in the BALB/c strain of mice (50 mg/kg at two times per week) (Lallo and Bondan 2005) and by Leishmania donovani (100 mg/kg/week) with retardation of the formation of the hepatic granulomas in hamsters (Corrêa et al 1992). However, use of cyclophosphamide at 60 mg/kg/week did not produce an effect on the humoral immune response or the larval burden of the nematode Brugia pahangi in the rodent, Meriones persicus (Katz and Lammie 1984), suggesting that the immunosuppressive activity of cyclophosphamide varies according to the dose, parasite species and the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The action of betamethasone (1 mg/kg/day), which was administered before and after the inoculation of the T. canis eggs, was studied, and this drug had no immunosuppressor effect (Lescano et al 2004). The immunosuppressor effect of cyclophosphamide was observed in an infection by Encephalitozoon cuniculi in the BALB/c strain of mice (50 mg/kg at two times per week) (Lallo and Bondan 2005) and by Leishmania donovani (100 mg/kg/week) with retardation of the formation of the hepatic granulomas in hamsters (Corrêa et al 1992). However, use of cyclophosphamide at 60 mg/kg/week did not produce an effect on the humoral immune response or the larval burden of the nematode Brugia pahangi in the rodent, Meriones persicus (Katz and Lammie 1984), suggesting that the immunosuppressive activity of cyclophosphamide varies according to the dose, parasite species and the host.…”
Section: Discussionmentioning
confidence: 99%
“…Groups 2 and 3 were treated with dexamethasone (Decadron®) of 1 and 5 mg/kg/day, respectively (Lallo et al 2002). Group 4 was treated with cyclophosphamide (Genuxal ®) of 50 mg/kg at two times per week (Lallo and Bondan 2005).…”
Section: Methodsmentioning
confidence: 99%
“…En el ámbito mundial, aunque existen referencias de modelos animales inmunosuprimidos para el estudio de la microsporidiosis, éstos se han enfocado hacia la caracterización clínica y parasitológica de la infección, principalmente por Encephalitozoon cuniculi (18)(19)(20), utilizando animales manipulados genéticamente o con fármacos que producen una supresión total de la respuesta inmune, como es el caso de los corticosteroides y la ciclofosfamida, los cuales no tienen acción selectiva sobre algunos de los componentes de la inmunidad.…”
unclassified
“…In humans, the infection was first described by Matsubayashi et al in 1959 and since then an increasing number of cases have been reported particularly in immunocompromised individuals. The clinical manifestations include ocular lesions (conjunctivitis, chorioretinitis), muscles (myositis), kidney (nephritis), neurological (encephalitis), liver (hepatitis), peritoneal (peritonitis) and others (Abreu-Costa, 2005;Lallo et al, 2002;Lallo & Bondan, 2005;Weber et al, 2002). Some species of microsporidia infecting invertebrates and can cause serious economic losses.…”
Section: About the Agent And The Diseasementioning
confidence: 99%